A new approach to measure radon by Thick Gas Electron Multiplier. (July 2022) - Arsia, Rahim; Salem, Mohammad Kazem; Negarestani, Ali; Sari, Amir Hossein
Abstract: In this article, a novel approach to the use of the Micro Pattern Gas Detector (MPGD) to detect the radon gas contamination in air is presented. It consists in operating the Thick Gas Electron Multiplier (THGEM) in Self-Quenched Streamer (SQS) mode. This detector works based on counting alpha particles emitted from radon and its short-lived daughters, Po-218 and Po-214. If this detector is compared to a scintillation detector, its THGEM can be considered as a scintillator and conventional light sensors as photomultipliers or sensitive photodiodes. A laboratory layout of the recommended system was designed to measure radon concentration in air based on measuring the alpha emitted of radon and its short-lived daughters. One of the advantages of this detector over the scintillation and semiconductor detectors is a vast sensitive surface (5*5 cm 2 ) uninfluenced by noises and background rays. The practical results show that this recommended detector uninfluenced by background rays has a very low limit of detection about zero. Consequently, this detector can measure very low radon gas concentrations in the air. Highlights: A new approach to measure radon by THGEM. Very low exposure to background radiation due to eliminating them. No preamplifier/amplifier, due to high ratio of signals to background radiation. Light is detected by cheap light sensors. The sensitive surface of detector is much bigger than that of semiconductor detector.